HUBUNGAN SIKAP DAN PENGETAHUAN SISWI TERHADAP KEPATUHAN KONSUMSI TABLET TAMBAH DARAH - Murnariswari, Kirana; Nuzrina, Rachmanida; Dewanti, Lintang P; Nadiyah, Nadiyah (Poltekkes Kemenkes Semarang, 2021)
Background: Anemia is one of the global public health problems which affect 1.62 billion world population. One of the government's programs to prevent and combat anemia on female adolescents are PPAGB programs with administration of one Fe tablet consumption once a week for a year. But not all female adolescents adhere to consume Fe Tablets which given from the program.Objective: To determine the correlation between female students' knowledge and attitude related with anemia on Fe-tablets compliance on PPAGB Programs in 26's National Junior High School (SMPN 26) Bekasi City, West Java. Method: A research survey with cross-sectional design. Sampling technique with systematic random sampling to obtain 100 respondents. Data were analyzed with Chi-Square test. Result: The results showed that attitudes and knowledge related to anemia were correlated with Fe-tablets consumption and compliance. The Chi-Square test showed the relationship between attitude and Fe-tablets compliance with p-value 0.000; 0.005, also relationship between knowledge related to anemia and Fe-tablets consumption with p-value 0.002; 0.005Conclusion: There are a relationship between female students' attitude and knowledge related to anemia on Fe-tablet compliance on PPAGB Program at 26's National Junior High School (SMPN 26) Bekasi City, West Java.